Electoral Incentives to Cultivate a Personal Vote and Political Particularism: a Text Analysis Approach - DECADRI, SILVIA (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2020)
In this dissertation, I examine the impact of electoral rules on political particularism. I study the legislative behaviour of Italian members of parliament (MPs) as a case study of how this causal mechanism works. To analyse the inner workings of the causal mechanism, I employ computational text analytic methods, multivariate regression analysis and a quasi- experiment. In Chapter 2, I produce the first and most extensive data-set on Italian proposed legislation, and I devise and validate a new methodology to capture particularistic policy-making by means of automated dictionary methods. The newly developed data-set and methodology will assist future analyses on particularistic policy-making in Italy and, more broadly, prospective studies on legislative activity and legislators? behaviour. In Chapter 3, I concentrate my analysis on postwar Italy, understood as the period that goes from 1948 to 1994. Conventional wisdom in Italian studies tells us that during the postwar period pork-barrel and clientelism were widespread. In this context, I employ data on the preference votes gained by each MP to scrutinise more in depth the well-established causal mechanism linking the construction of a personal vote to the promotion of particularistic policy-making. In Chapter 4, I use the peculiar features of the Italian mixed-member electoral system operating from 1994 to 2006 to obtain analytic leverage on the causal mechanism linking electoral rules to particularistic policy-making. My analysis confirms that legislators with strong personal followings are more willing to favour parochial interests. Still, my study does not find empirical evidence of a purely causal connection between the electoral rule and political particularism and it proposes the strength of legislators? local connections and the interaction between electoral rules and regulations as further significant contributory factors.
APPROVED
Keywords: Electoral systems; Automated text-analysis; Legislative behaviour; Italy